Mobilizing Voices: A Discussion of Leadership in an Environmentally Contaminated Community - Robinson, Erin E. (Qualitative Sociology Review, 2009)
Leadership is a key factor in successful social movement mobilization. Without a grasp of leadership dynamics in a community, it is difficult to explain how individuals come to occupy leadership roles and what impact this has on the overall success of a movement effort. In this study, I use the qualitative approach to investigate how leadership is framed in a community facing the existence of environmental contamination. I follow the development of leadership among actors and particularly the relationships that they create and maintain with expert environmental activists. Using interview data from 35 community residents and activists, I establish how leadership frames were presented to the community and how these frames impacted mobilization efforts and outcomes.